Intervensi Gizi untuk Penanganan Terjadinya Gizi Kurang pada Balita Usia Dibawah Lima Tahun - Wiwien Ellora Ester Riang Harefa; Tuty Hertati Purba (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2025)
Toddlers are children under five years old who experience rapid growth and development, requiring adequate nutrition. However, they are also vulnerable to nutritional problems such as stunting, obesity, overweight, and undernutrition. The main cause of these issues is inadequate nutrient intake that does not meet their needs. Various efforts have been made to address this, including supplementary feeding (PMT), health promotion, counseling, immunization, and monitoring of growth and development. This study aims to identify effective nutritional interventions for addressing undernutrition in toddlers. A systematic review was conducted based on PRISMA-ScR. Articles were sourced from Science Direct, PubMed, DOAJ, Google Scholar, and Garuda using the keywords nutrition intervention OR underweight AND toddler. Out of 765 articles found, six met the inclusion criteria. The findings indicate that nutritional interventions can be categorized into PMT and nutrition education, with an average intervention duration of three months for children aged 6–59 months. The Emo Demo method was found to be twice as effective in improving nutritional status based on the BB/U and BB/TB indices. In conclusion, the Emo Demo method can be an effective intervention choice to combat undernutrition in toddlers.